Thermal proteome profiling reveals fructose-1,6-bisphosphate as a phosphate donor to activate phosphoglycerate mutase 1 - Yanling Zhang; Yafei Cao; Xia Wu; Zhenghui Chen; Bowen Chen; Anhui Wang; Yanshen Guo; Wei Chen; Ruolan Xue; Zihua Liu; Yuanpei Li; Tian Li; et al. (Nature Communications)
Abstract Deep understanding of sugar metabolite-protein interactions should provide implications on sugar metabolic reprogramming in human physiopathology. Although tremendous efforts have been made for determining individual event, global profiling of such interactome remains challenging. Here we describe thermal proteome profiling of glycolytic metabolite fructose-1,6-bisphosphate (FBP)-interacting proteins. Our results reveal a chemical signaling role of FBP which acts as a phosphate donor to activate phosphoglycerate mutase 1 (PGAM1) and contribute an intrapathway feedback for glycolysis and cell proliferation. At molecular level, FBP donates either C1-O-phosphate or C6-O-phosphate to the catalytic histidine of PGAM1 to form 3-phosphate histidine (3-pHis) modification. Importantly, structure-activity relationship studies facilitate the discovery of PGAM1 orthostatic inhibitors which can potentially restrain cancer cell proliferation. Collectively we have profiled a spectrum of FBP interactome, and discovered a unique covalent signaling function of FBP that supports Warburg effect via histidine phosphorylation which inspires the development of pharmacological tools targeting sugar metabolism.